Comparative histomorphometric analysis between α-Tcp cement and β-Tcp/Ha granules in the bone repair of rat calvaria - Grandi,Gisela (2011)
This study compared the effect of two bioceramics on the process of bone repair: α-tricalcium phosphate (α-TCP) cement and β-tricalcium phosphate hydroxyapatite particles (β-TCP/HA). Calvarial defects were created in 50 rats, divided into two groups (α and β/HA). Software was used at 7, 21, 60, 90 and 120 days to assess bone formation. Mean new bone formation rates were as follows: α group, 1.6% at 7 days, 5.24% at 21 days, 24% at 60 days, 30.21% at 90 days and 50.59% at 120 days; β/HA group, 1.94% at 7 days, 2.53% at 21 days, 12.47% at 60 days, 26.84% at 90 days and 38.82% at 120 days; control group, 0.15% at 7 days, 10.12% at 21 days, 15.10% at 60 days, 18.94% at 90 days, 48.50% at 120 days. Both materials are osteoconductive and biocompatible. Perhaps the larger rate of new bone formation observed in the α-TCP group, it also occurs in the β-TCP/HA group within a longer time period.